2010
DOI: 10.3109/17453671003635884
|View full text |Cite|
|
Sign up to set email alerts
|

Plate fixation or intramedullary fixation of humeral shaft fractures

Abstract: BackgroundThe optimal approach to operative treatment of humeral shaft fractures remains debatable. Previously published trials have been limited in size and have been inconclusive regarding important patient outcome variables following treatment with either intramedullary nails or plates. We conducted a meta-analysis of available trials comparing treatment of humeral shaft fractures.Methods We performed a literature search from 1967 to November 2007 in the main medical search engines and selected 4 randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
3
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 24 publications
1
36
3
8
Order By: Relevance
“…Changulani et al found that infection rates after plate osteosynthesis are four times higher than with IMN [32]. A recent meta-analysis confirmed that there is a significant correlation between plate osteosynthesis and infection, although this difference has not been reported in other publications [20,30,33,34].…”
Section: Discussionmentioning
confidence: 79%
“…Changulani et al found that infection rates after plate osteosynthesis are four times higher than with IMN [32]. A recent meta-analysis confirmed that there is a significant correlation between plate osteosynthesis and infection, although this difference has not been reported in other publications [20,30,33,34].…”
Section: Discussionmentioning
confidence: 79%
“…여러 저자들에 의해서 두 수술 술기 간 장점과 단점이 비교되었으나 [5][6][7][8][9][10][11][12] , 일반적인 상완골 간부 골절에 대한 비교에서 두 수술 술기 간에 유합률은 차이를 보이지 않는 것으로 보고되고 있다 [5][6][7][8][9][10][11][12] . 단순 상완골 간부 골절과 비교하여 골절부에 나비형 골편이 동반된 경우, 내고정 시 고정물의 생역학적 고정력에 영향을 주게 되어 13) , 나비형 골편의 전위에 따라 고정력과 유합률에 영향을 받을 수 있다 14,15) .…”
Section: 상완골 간부 골절의 수술적 치료 방법으로는 금속판 고정과unclassified
“…1,4,11 Union rates may depend on many factors, including type of the fracture, patient-specific factors, status of smoking, age, gender, bone quality, severity of trauma, and loss of fracture hematoma secondary to open reduction. 12 In terms of length of hospital stay, while minimal length of stay (2 days) was the same in both groups, one patient in IMN group received in-hospital antibiotics of 7 days due to superficial soft tissue infection, which increased mean length of stay in the latter group. Although statistically not significant, lower length of hospital stay in AIMN group may be explained by less invasive and soft tissue-friendly nature of the performed technique.…”
Section: Discussionmentioning
confidence: 86%